Implications of Data Screens on Merger and Acquisition Analysis: A Large Sample Study of Mergers and Acquisitions from 1992 to 2009 - Netter, Jeffry; Stegemoller, Mike; Wintoki, M. Babajide (Review of Financial Studies, 2011)
We analyze a comprehensive set of mergers and acquisitions from SDC data from 1992 through 2009. We do not impose common restrictions such as excluding private bidders, small targets, or deals without a deal value. We show a broader scope of mergers and acquisitions activity than that implied in the literature, which generally oversamples larger deals involving public firms. Further, some of our results differ from the extant literature. For example, the finding that mergers occur in waves is attenuated with a greater presence of smaller and/or non-public firms. Also, acquirers gain in most takeovers despite a threefold decline over the sample period in acquirer returns.